The Effect of Advertising, Prices, and Public Relations on Red and White Cement Purchase Decisions in Gresik Regency - Mukhammad Alfan Abdillah; Moh Agung Surianto (INNOVATION RESEARCH JOURNAL, 2023)
The background in this research is the sale of Semen Merah Putih does not meet the target. This study aims to examine the influence of advertising, price, and public relations on the purchasing decision of Red and White Cement in Gresik Regency. This study uses quantitative methods. The population in this study were consumers who had purchased Semen Merah Putih products, while the sample was taken using the Probability Sampling technique using simple random sampling. The reason is because of the way of taking samples from members of the population using random regardless of the strata (levels) in the members of the sample population. The sample studied by the researcher was 96 96 people who had made a purchase of Red and White Cement products. The analysis technique uses instrument testing, classical assumption test, and hypothesis testing. For the test tool, the Statistical Package for the Social Sciences (SPSS) is used. The results of this study indicate that advertising has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, and public relations has a positive and significant effect on purchasing decisions.